EFEKTIFITAS PENGGUNAAN MEDIA PEMBELAJARAN MATEMATIKA BERBAHAN SAMPAH UNTUK MENGURANGI LEARNING LOSS AKIBAT PANDEMI COVID-19 - Deda, Yohanis Ndapa; Disnawati, Hermina (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2022)
During the Covid-19 pandemic, there was a change in the education system, namely regular or face-to-face learning suddenly changed to learning from home (BDR). One of the difficulties is the change in the direct learning climate to online learning, which is done individually. This difficulty resulted in learning loss for students. Learning loss has a long-term negative impact, namely reduced student academic achievement and cognitive skills. Therefore, it is necessary to choose learning media to minimize learning loss due to BDR during the Covid-19 pandemic. One learning media that is suitable for the conditions of the learning community in Kefamenanu City is the Mathematics learning media made from Waste (MPMBS), namely positive and negative charges. This study aims to reduce learning loss for students in the learning community in the city of Kefamenanu. The type of research is an experimental, pre-Experimental Design, namely a One-Group Pretest-Posttest with 11 students in the Sunday school community at one of the GMIT Churches in Kefamenanu. Data collection methods are tests, questionnaires and documentation. The data analysis techniques are descriptive statistical analysis, N-Gain analysis and inferential analysis. The results showed that the average value of the pretest was 33, and the average value of the posttest was 57.17. There was an increase after the students were given the learning treatment using MPMBS with a charge of 27.57 and an average N-gain of 0.64, including the medium category. Based on the results of this study, it can be concluded that the use of waste-based MPMBS in learning integer operations can improve learning achievement while reducing learning loss in the community of Sunday school children in Kefemenanu. The next plan that will be done is to analyze the level of motivation of respondents to the use of MPMBS